Resettlement experiences and resilience in refugee youth in Perth, Western Australia - Earnest, Jaya; Mansi, Ruth; Bayati, Sara; Earnest, Joel; Thompson, S. (BioMed Central, 2015)
Background: In Australia, the two major pathways of refugee entry are the United Nations High Commissioner for Refugees resettlement programme and irregular maritime arrivals (IMAs) seeking asylum. The Australian Government’s policies towards IMAs since July 2013 are controversial, uncompromising and consistently harsh, with asylum seekers held in detention centres for prolonged periods. Refugees and asylum seekers have distinct and unique stressors that make resettlement difficult. Methods: This exploratory study examines resettlement experiences for refugee youth in Western Australia using the psychosocial conceptual framework and qualitative methods. Focus group discussions and key informant interviews were undertaken with verbatim transcripts analysed using thematic analysis to identify themes. Results: Themes documented that language and its impact, and experience with education, health, and social activities, support structures provided to youth and supporting future aspirations as critical to successful resettlement. This exploratory study contributes to developing a broader understanding of the resettlement experiences of refugee youth, drawing on their current and past experiences, cultural differences and mechanisms for coping. Conclusion: Fluency in English language, especially spoken, was a facilitator of successful resettlement. Our results align with previous studies documenting that support programs are vital for successful resettlement. Although faced with immense difficulties refugee youth are resilient, want to succeed and have aspirations for the future. Strategies and recommendations suggested by refugee youth themselves could be used for developing interventions to assist successful resettlement.